Arabica coffee seedlings production in substrate composed by residue from grains drying process - Meneghelli, Lorena Aparecida Merlo; Lo Monaco, Paola Alfonsa Vieira; Haddade, Ismail Ramalho; Meneghelli, Caroline Merlo; Krause, Marcelo Rodrigo; Vieira, Gustavo Haddad Souza (Coffee Science - ISSN 1984-3909, 2017)
This study aimed to evaluate the use of “moinha” in the composition of an alternative substrate for the production of Arabica coffee plants, ‘Catuaí Vermelho’ IAC-99 cultivar. The experimental design was a completely randomized design with five treatments, that were four proportions of “moinha” (10, 20, 30 and 40% of the volume of the substrate mixed with the soil) and a control substrate (soil and manure in the proportion of 3: 1) on the arabica coffee seedlings. The variables evaluated were: number of leaves, plant height, shoot diameter, shoot and root dry matter, total dry matter and substrate electrical conductivity, all performed at 180 days after sowing. The increase in the concentration of “moinha” promotes the increase of electric conductivity in the substrates. Concentrations from 10% until 30% of “moinha” in the substrate composition can be used as an alternative to the use of substrate with bovine manure and without supply of nutrients via fertilizers. However, the concentration of 20% of “moinha” in the substrate composition promotes the highest values of number of leaves, shoot diameter and root dry matter.